Co-creation in theory and practice : exploring creativity in the global North and South - Horvath, Christina; Carpenter, Juliet (Policy Press, an imprint of Bristol University Press, 2020)
This book analyses a diverse range of experiences of Co-Creation in neighbourhood settings across the Global North and Global South. It brings together a unique collection of researchers, artists, residents and policymakers, all exploring creative ways to address neighbourhood challenges and effect change towards more socially just cities.